2005
DOI: 10.1002/cncr.20871
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits, health behavior, and risk for cancer

Abstract: Background Sharps injuries (SI) and other blood/body fluid exposures (BBFE) present bloodborne pathogen risks for home healthcare (HHC) workers. While SI and BBFE are sufficiently frequent in HHC to be serious public health concerns, even moderately large surveys can still have insufficient power to identify risk factors. In this study, a new conceptual model for using near‐misses for SI and BBFE was developed and its utility in statistical analyses of SI and BBFE risk factors was evaluated. Methods A survey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 43 publications
(58 reference statements)
4
29
2
4
Order By: Relevance
“…The results of our earlier prospective cohort studies, however, do not support the hypothesis that personality traits measured by the Eysenck questionnaire are associated with risk for cancer (Schapiro et al, 2001;Nakaya et al, 2003;Hansen et al, 2005).…”
contrasting
confidence: 89%
“…The results of our earlier prospective cohort studies, however, do not support the hypothesis that personality traits measured by the Eysenck questionnaire are associated with risk for cancer (Schapiro et al, 2001;Nakaya et al, 2003;Hansen et al, 2005).…”
contrasting
confidence: 89%
“…In none did we find evidence for an independent link between psychological factors such as severe depression (Dalton et al, 2002), personality traits (Hansen et al, 2005) or stressful life events (Li et al, 2002;Dalton et al, 2004) and cancer risk. We conclude that there is no convincing evidence that psychological factors cause cancer.…”
Section: Discussioncontrasting
confidence: 58%
“…Psychological factors, such as certain personality traits, depression, and major life events, are thought to contribute to the pathogenesis of cancer (Hansen et al, 2005). The results from retrospective and prospective studies support an association between the two personality traits -neuroticism and extraversion-and cancer risk (Kissen et al, 1969;Aarstad et al, 2002).…”
Section: Introductionmentioning
confidence: 84%
“…Since then, the results of several wellconducted prospective studies have not confirmed the association between personality traits such as extraversion, neuroticism, trait anxiety and cancer risk (Ratcliffe et al, 1995;Schapiro et al, 2001;Nakaya et al, 2003;Hansen et al, 2005). However, the majority of these studies had methodological limitations due to the small number of cases or the lack of powered analysis.…”
Section: Discussionmentioning
confidence: 99%